2010
DOI: 10.1037/a0019372
|View full text |Cite
|
Sign up to set email alerts
|

Increased attention but more efficient disengagement: Neuroscientific evidence for defensive processing of threatening health information.

Abstract: The findings provide the first neuroscientific support for the hypothesis that threatening health information causes more efficient disengagement among those for whom the health threat is self-relevant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
132
2
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 122 publications
(144 citation statements)
references
References 45 publications
8
132
2
2
Order By: Relevance
“…However, when efficacy is low people will not adopt the desired health behavior but will choose to control the feeling of fear by engaging in defensive processes (e.g., defensive avoidance; Witte, 1992;Witte & Allen, 2000). In line with this, several studies have found that smokers more efficiently disengage attention from highly threatening than lowthreatening or nonthreatening stimuli (Kessels, Ruiter, & Jansma, 2010;Maynard, Munafò, & Leonards, 2013). Thus, for a significant proportion of smokers a fear-eliciting message that stresses negative outcomes of smoking is likely to be ineffective.…”
Section: Gains Versus Lossesmentioning
confidence: 71%
“…However, when efficacy is low people will not adopt the desired health behavior but will choose to control the feeling of fear by engaging in defensive processes (e.g., defensive avoidance; Witte, 1992;Witte & Allen, 2000). In line with this, several studies have found that smokers more efficiently disengage attention from highly threatening than lowthreatening or nonthreatening stimuli (Kessels, Ruiter, & Jansma, 2010;Maynard, Munafò, & Leonards, 2013). Thus, for a significant proportion of smokers a fear-eliciting message that stresses negative outcomes of smoking is likely to be ineffective.…”
Section: Gains Versus Lossesmentioning
confidence: 71%
“…These findings are in line with empirical evidence showing that past behavior enhances persuasive effects of framed messages. 39,40,50 This may be because people who already adhere to public health guidelines are more involved with health behavior(s), 40,51,52 which has been shown to moderate message framing effects. 33 What is perhaps more concerning is that the current findings revealed problematic issues when attempting to persuade those most in need of being persuaded (eg, have insufficient fruit intake).…”
Section: Discussionmentioning
confidence: 96%
“…However, participants may become less defensive over time. Repeated exposure of injunctive messages has been found to be effective in reducing smoking (Kessels et al, 2010), drinking (Brown & Locker, 2009), and risky sexual behavior (Earl et al, 2009).…”
Section: Discussionmentioning
confidence: 99%